1979
DOI: 10.1007/bf01907686
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of myocardial action potential in left ventricular hypertrophy of Goldblatt rats

Abstract: Action potentials were measured in hypertropl~ied rat myocardium by means of glass microelectrodes. Left ventricular hypertrophy was induced by experimental chronic coarctation of one renal artery without contralateral nephrectomy. The action potentials of the hypertrophied myocardium exhibit a marked prolongation without any significant changes in the transmembrane resting potential, in the amplitude, or in the maximum upstroke velocity of the action potential. The increase in the half-width of the action pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…In cats showing evidence of congestive heart failure, the action potentials showed marked alterations . In contrast to the variable electrophysiological changes observed in cats with right ventricular hypertrophy, we (Aronson, 1980) and others (Gulch et al, 1979) have found substantial and consistent prolongation of action potentials in rats with left ventricular hypertrophy induced by renal hypertension. In addition, it has been reported that spontaneously hypertensive rats (Hayashi and Shibata, 1974;Heller and Stauffer, 1979) and rats made hypertensive with deoxycorticosterone acetate (Heller and Stauffer, 1979) have longer action potentials than do control rats.…”
Section: Figure 5 Relation Between Recording Site and DCL Independentcontrasting
confidence: 80%
See 3 more Smart Citations
“…In cats showing evidence of congestive heart failure, the action potentials showed marked alterations . In contrast to the variable electrophysiological changes observed in cats with right ventricular hypertrophy, we (Aronson, 1980) and others (Gulch et al, 1979) have found substantial and consistent prolongation of action potentials in rats with left ventricular hypertrophy induced by renal hypertension. In addition, it has been reported that spontaneously hypertensive rats (Hayashi and Shibata, 1974;Heller and Stauffer, 1979) and rats made hypertensive with deoxycorticosterone acetate (Heller and Stauffer, 1979) have longer action potentials than do control rats.…”
Section: Figure 5 Relation Between Recording Site and DCL Independentcontrasting
confidence: 80%
“…For example, in a morphometric study of hypertrophied left ventricles from rats with renal hypertension, Loud et al (1978) and Anversa et al (1978) reported a greater enlargement of epicardial cells than endocardial cells after 1-4 weeks of hypertension. In the same model, Aronson (1980) recently reported a 50% prolongation of action potential duration in hypertrophied rat papillary muscle driven at a cycle length of 1000 msec (35°C), and Gulch et al (1979) reported a 180% increase in action potential duration in left ventricular trabeculae driven at a cycle length of 5000 msec (25°C). These results suggest that hypertrophy induced by renal hypertension may be a non-uniform process that affects endocardial, papillary muscle, and epicardial fibers to a different degree.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…We (12) and others (29,21,3,35,36) have shown that in the renal hypertensive rat there are considerable alterations in the cell membrane as evidenced by dramatic prolongation of the transmembrane action potential. It has also been shown that people with hypertensive hypertrophy have an increased susceptibility to ventricular arrhythmias and that these arrhythmias might very well cause sudden death in this population.…”
Section: Introductionmentioning
confidence: 97%